Obesity Enhances Antioxidant Capacity and Reduces Cytokine Levels of the Spleen in Mice to Resist Splenic Injury Challenged by Escherichia coli - Xuchu Gu; Zhiyu Ma; Jing Fang; Dongjie Cai; Zhicai Zuo; Shuang Liang; Hengmin Cui; Junliang Deng; Xiaoping Ma; Zhihua Ren; Yi Geng; Ming Zhang; et al. (Journal of Immunology Research)
Obese mice exhibited more lymphocytes in the bronchoalveolar lavage fluid and milder lung injury after Escherichia coli (E. coli) infection. However, it remained unclear whether the spleen contributed to the effect of obese mice with infection. The study was purposed to reveal the histopathological changes of the spleen caused by oxidative stress and inflammation in diet-induced obesity (DIO) mice challenged by Escherichia coli. After infection, the spleen tissues were obtained in normal and DIO mice at 0 h (uninfected), 12 h, 24 h, and 72 h postinfection. Results revealed that DIO mice have higher contents of resistin, TNF-α, IL-6, and IL-1β in the spleen than normal mice and lower concentrations of GSH-Px, SOD, and CAT and higher MDA than normal mice. After an intranasal drip of E. coli, the activities of GSH-Px, SOD, and CAT in the DIO mice were elevated and the content of MDA declined. The activities of SOD and CAT in the normal mice declined, and the content of MDA was elevated. Moreover, the contents of TNF-α, IL-6, and IL-1β in the spleen declined in DIO mice at 24 and 72 h, although the contents of leptin, resistin, TNF-α, IL-6, and IL-1β were elevated at 12 h. The contents of resistin, TNF-α, IL-6, and IL-1β were elevated in normal mice at 12 and 24 h. Those results indicated that obesity elevated splenic oxidation and inflammatory levels, but it enhanced antioxidant capacity and reduced cytokine levels of the spleen in mice to resist splenic injury after an intranasal drip of E. coli.